HIF1α Regulates IL17 Signaling Pathway Influencing Sensitivity of Taxane-Based Chemotherapy for Breast Cancer - Dai, Huijuan; Sheng, Xiaonan; Wang, Yaohui; Zhou, Liheng; Lin, Yanping; Du, Yueyao; Yang, Fan; Sha, Rui; Peng, Jing; Yao, Linli; Yin, Wenjin; Lu, Jinsong (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia-induced chemotherapy resistance is the main hindrance for solid tumor treatment. Hypoxia inducible factor-1α (HIF1α), an adaptive gene of hypoxia condition, played an important role in affecting chemotherapy sensitivity for many cancer types and various therapeutic regimens. This study focused on the impact of HIF1α on predicting response and survival of taxane-based neoadjuvant therapy (NAT) for breast cancer (BC) patients and the concrete mechanism that HIF1α mediated paclitaxel chemo-insensitivity. We evaluated HIF1α expression immunohistochemically from biopsies of 108 BC patients receiving paclitaxel–cisplatin NAT. Univariate and multivariate logistic regression analysis revealed that high HIF1α expression led to lower rate of pathological complete response (pCR) and worse prognosis. Analysis of GEO datasets also indicated negative association between HIF1α expression and response of taxane-based NAT in BC patients. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment of differential expression genes (DEGs) in different HIF1α expression groups from TCGA database showed that HIF1α participated in interleukin 17 (IL-17) signaling pathway. Correlation analysis suggested that HIF1α was positively related to the IL-17 pathway. CXC motif chemokine ligand 10 (CXCL10) was the only DEG in the IL-17 pathway inversely relating to NAT response. Experiments in vitro verified that HIF1α/IL-17 pathway influences paclitaxel sensitivity to BC cells. Correlation analysis between HIF1α/IL-17A/CXCL10 and infiltration of immune cells in BC uncovered that high expression of all the above three genes were positively correlated to neutrophil infiltration in BC. Collectively, our findings shed novel insight into the mechanism of chemotherapy resistance and implied that HIF1α inhibitor may be a promising drug combined with traditional chemotherapeutic drug to increase the chemotherapy efficacy.